Answer:
D. 1
Step-by-step explanation:
We have the expression, ![\frac{\csc^{2}x\sec^{2}x}{\sec^{2}x+\csc^{2}x}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ccsc%5E%7B2%7Dx%5Csec%5E%7B2%7Dx%7D%7B%5Csec%5E%7B2%7Dx%2B%5Ccsc%5E%7B2%7Dx%7D)
We get, eliminating the cosecant function,
![\frac{\sec^{2}x}{\frac{\sec^{2}x}{\csc^{2}x}+1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csec%5E%7B2%7Dx%7D%7B%5Cfrac%7B%5Csec%5E%7B2%7Dx%7D%7B%5Ccsc%5E%7B2%7Dx%7D%2B1%7D)
As, sinx is reciprocal of cosecx and cosx is reciprocal of secx,
i.e. ![\frac{\sec^{2}x}{\frac{\sin^{2}x}{\cos^{2}x}+1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csec%5E%7B2%7Dx%7D%7B%5Cfrac%7B%5Csin%5E%7B2%7Dx%7D%7B%5Ccos%5E%7B2%7Dx%7D%2B1%7D)
i.e. ![\frac{1}{\cos^{2}x}\times \frac{\cos^{2}x}{\sin^{2}x+\cos^{2}x}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Ccos%5E%7B2%7Dx%7D%5Ctimes%20%5Cfrac%7B%5Ccos%5E%7B2%7Dx%7D%7B%5Csin%5E%7B2%7Dx%2B%5Ccos%5E%7B2%7Dx%7D)
Since, we know that, ![\sin^{2}x+\cos^{2}x=1](https://tex.z-dn.net/?f=%5Csin%5E%7B2%7Dx%2B%5Ccos%5E%7B2%7Dx%3D1)
Thus,
![\frac{1}{\cos^{2}x}\times \frac{\cos^{2}x}{\sin^{2}x+\cos^{2}x}=1](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Ccos%5E%7B2%7Dx%7D%5Ctimes%20%5Cfrac%7B%5Ccos%5E%7B2%7Dx%7D%7B%5Csin%5E%7B2%7Dx%2B%5Ccos%5E%7B2%7Dx%7D%3D1)
So, after simplifying, we get that the result is 1.
Hence, option D is correct.
Step-by-step explanation:
<u>Given</u>
- f(x) = 4x³ + 3x² - 2x - 1
<u>Divide it by the following:</u>
<u>(a) 2x + 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 2x²) + (x² + 1/2x) - (5/2x + 5/4) + 1/4 =
- 2x²(2x+1) + 1/2x(2x + 1) - 5/4(2x + 1) + 1/4 =
- (2x + 1)(2x² + 1/2x - 5/4) + 1/4
Quotient = 2x² + 1/2x - 5/4
Remainder = 1/4
<u>(b) 2x - 3</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - 6x²) + (9x² - 13.5x) + (11.5x - 17.25) + 16.25 =
- (2x -3)(2x² + 4.5x + 5.75) + 16.25
Quotient = 2x² + 4.5x + 5.75
Remainder = 16.25
<u>(c) 4x - 1</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ - x²) + (4x² - x) - (2x - 1/2) - 3/2 =
- (4x - 1)(x² + x - 1/2) - 3/2
Quotient = x² + x - 1/2
Remainder = - 3/2
<u>(d) x + 2</u>
- 4x³ + 3x² - 2x - 1 =
- (4x³ + 8x²) - (5x² + 10x) + (8x + 16) - 17 =
- (x + 2)(4x² - 5x + 8) - 17
Quotient = 4x² - 5x + 8
Remainder = - 17
12 x 12 = 144
20 x 12 = 240
=384
ANSWER: 384
Answer:
Step-by-step explanation: